SunTzu on Battlegrounds and Strategies: Seven Propositions for Successful Market Targeting and Penetration Strategies for SMEs - Soo Jiuan Tan,; Khai Sheang Lee,; Guan H Lim, (Asian Academy of Management Journal, 1998)
SunTzu on Battlegrounds and Strategies: Seven Propositions for Successful Market Targeting and Penetration Strategies for SMEs(PDF not available)